1992
DOI: 10.1071/ph920683
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Shifts of Refractive Indices from Obliquely Propagating Waves in a Magnetised Plasma in the Presence of Coriolis Rotation

Abstract: This paper provides an expression for the nonlinear shifts of refractive indices from obliquely propagating waves in a cold, homogeneous, magnetised rotating plasma in the presence of a Coriolis force. The effects of gyrofrequency, rotational frequency, and the amplitude of the waves on the nonlinear shifts of refractive indices are discussed. It is found that these parameters play a dominant role in the nonlinear shifts of refractive indices and the results are more general than those of earlier workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Deschamps et al (1970) experimentally observed that a uniform magnetisation of the order of 10-2 G is generated in a plasma by a pulsed microwave signal having frequency 3000 MHz and a repetition frequency of 10 Hz. In the present investigation the power of the EM wave is below the threshold power obtained by Kaw and Dawson (1970), so our results will have physical significance for laboratory experiments and space plasmas. As the induced magnetisation observed by Deschamps et al (1970) is very low in comparison with the static magnetic field used in numerical calculations, the IFE is neglected in the present analysis.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Deschamps et al (1970) experimentally observed that a uniform magnetisation of the order of 10-2 G is generated in a plasma by a pulsed microwave signal having frequency 3000 MHz and a repetition frequency of 10 Hz. In the present investigation the power of the EM wave is below the threshold power obtained by Kaw and Dawson (1970), so our results will have physical significance for laboratory experiments and space plasmas. As the induced magnetisation observed by Deschamps et al (1970) is very low in comparison with the static magnetic field used in numerical calculations, the IFE is neglected in the present analysis.…”
Section: Discussionmentioning
confidence: 81%
“…In recent years, several authors have studied the effects of nonlinearity on wave propagation in relativistic plasmas (Lerche 1967(Lerche , 1969Kaw and Dawson 1970;Winkles and Eldridge 1972;Stenflo et al 1983;Kennel and Pellat 1976;Shih 1978;Stenflo and Tsinstadze 1979;Hora 1981;Tsytovich and Stenflo 1983;Shukla et al 1986). It has been found that relativistic mass correction effects for electron and ion motions are significant in the shift of wave parameters (Sluijter and Montgomery 1965;Tidman and Stainer 1965;Boyd 1967;Das 1968Das , 1971Chandra 1974), precessional rotation (Arons and Max 1974;Lai and Wonnacott 1976;Chakraborty 1977;Khan and Chakraborty 1979;Chakraborty 1979, 1982;Bhattacharyya 1983;, the IFE (Steiger and Woods 1972), solitons and shocks (Das and Paul 1985;Nejoh 1987Nejoh , 1988Das et al 1988;Roy Chowdhury et al 1988, 1989a,b, 1990Salauddin 1990;Chakraborty et al 1992) and other nonlincar phenomena (Das and Sihi 1977;Shih 1978) in plasma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations